Peningkatan Membaca Mufrodat Bahasa Arab Siswa Melalui Media Pup up Book MDTA Banun-Banat Cipulus - Taufik Luthfi; Yayu Wahyudah; Muhammad Kholil (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
The aim of this research is to determine competence in reading mufrodat in learning Arabic using Pup Up Book Media at MDTA Banun - Banat. The research method uses quantitative research methods with a pre-experimental design. Pre-experimental design research in one-group form, using pre-experiments in one class, there is a pre-test (x) and a post-test (y) in order to find out whether or not the effect between before and after in use. This media is to improve understanding of memorizing mufrodat. Research data was collected from primary data and secondary data sources with data collection techniques using documentation, observation and interviews. The research uses a process of data reduction, data presentation, and drawing conclusions to analyze the data. The findings show that: Arabic language learning at MDTA Banun - Banat supports Arabic language learning outcomes.